Greening International Jurisprudence Environmental NGOs before International Courts, Tribunals, and Compliance Committees - Zengerling, Cathrin (Legal Aspects of Sustainable Development, 2013)
Greening International Jurisprudence: Environmental NGOs before International Courts, Tribunals, and Compliance Committees examines how international judicial and quasi-judicial bodies enforce international environmental law, with particular consideration to the role of environmental NGOs. Author Cathrin Zengerling analyses the institutional structure as well as the environmental case law from a total of fourteen international courts, arbitral tribunals, and compliance committees with special focus on accessibility, comprehensiveness, and transparency. Underlying this analysis is the fundamental question of whether the respective body appropriately contributes to the realization of democratic governance for sustainable development. After presenting her core findings, the author provides concrete recommendations for future best practices and discusses the need for a new World Environment Court.; Readership: